Condición socioeconómica y educación financiera de los estudiantes de la Escuela de Educación Básica Municipal “Héroes del Cenepa” de la ciudad de Loja - Sandoval Coronel, Camila Alejandra (2024)
One area that significantly impacts a person's overall development is financial education. Hence, experts recommend acquiring financial skills from an early age to make informed decisions about the correct management of personal finances. For this reason, the objective of this research is to determine the socioeconomic condition and the level of financial education of the students of the Escuela Básica Municipal “Héroes del Cenepa” through mixed experimental research using the PISA methodology and Bloom's taxonomy. The research design is transversal and quasi-experimental since the population was chosen without a random selection process. In addition, survey and evaluation techniques were used to collect information, in the first phase to determine the socioeconomic condition and the children's level of financial education, and in the second phase to determine whether the strategy improved the children's financial knowledge. The main findings are that the children of this institution were in the first quartile of level 3 of financial education before the implementation of the strategy; that no household socioeconomic variable affected their financial knowledge; and that, after socializing the financial education guide proposed as a strategy, the children moved to the fourth quartile of level 4 of financial education. To conclude, it was demonstrated that the guide helped reinforce the topics where the children had less mastery, allowing them to improve their understanding of concepts strictly related to finance.